Becoming a Living Prayer: Insights on the Integration of Prayer and Action from the Franciscan Tradition - Horan, Daniel P. (Concilium, 2024)
This article explores the relationship between prayer and action, examining the way these two dynamics of the spiritual life intersect and inform one another in ways often overlooked. The author draws on the model of Francis of Assisi tradition to illustrate what the openness to and experience of the transcendent in quotidian human experience looks like. As Thomas of Celano, Francis's first biographer, notes about the integration of prayer and action in his life, Francis sought to move from saying prayers to a way of life that was "totally prayer" through every word and deed. Examples of this transformation of the understanding of prayer as action can be seen in Francis's outreach to lepers, interreligious friendship, and creational spirituality.